PENGELOLAAN PARKIR DI TEPI JALAN UMUM DI KOTA PADANG - Meita Lefi Kurnia dan Harifal Swandi (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
One of the characteristics of regional financing in implementing autonomy is the source of Local Own Revenue (PAD), which consists of the results of local taxes, the results of regional retribution and the results of the management of local wealth that is separated as a major component of APBD sources. In order to increase PAD, the Government must first know what is the source of the PAD. Potential and potential revenue source sources are Parking Levies on the Public Roads as set forth in Article 1 of Padang City Regional Regulation No. 1 of 2016 on the Second Amendment to Padang City Regulation Number 11 Year 2011 on Public Service Levies stating